Transformational Changes in Demand and Supply on Food Markets during COVID-19 Pandemic - T. P. Maksimova; N. E. Bondarenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article studies specific features of transformational changes both in national economy in general and on sectoral markets in particular due to COVID-19 pandemic. It is shown that we can observe fundamental transformation of customer behavior towards the increasing demand for goods providing essential needs, which in the future can result in shaping new sustainable behavior models on food market. It proves the necessity to control prices on the part of state. By researching economic effects of transforming the structure of foods consumption and their supply the authors draw a conclusion that the key share in production structure and dynamic of agricultural produce output belongs to big economic forms, they also put forward a hypothesis about keeping the trend towards integration on the part of supply. The trends identified by the authors in the field can give an opportunity to devise in the future alternative models of scenario forecasts of trends in developing small and large economic structures in the effective institutional conditions. The article also studies the importance of product customization as a factor of sustainability of small economic structures.